Prototipe Perancangan Sistem Kendali Jarak Jauh Pada Traktor Roda 2 Menggunakan Arduino - Poerbaningtyas E; Candra Hadi Pranata (LPPM STIKI MALANG, 2023)
Seeing the conditions in this modern era, many farmers use the help of tools to work on land management, namely the two-wheeled tractor with the quick brand dragonfly model, where this tool has several advantages and disadvantages. An example of the advantages of the quick brand dragonfly model tool is that it has a minimalist design and an affordable price. While the weakness of the tractor tool is that the dragonfly model tractor tool with the Quick brand is still conventional or manual. In order to overcome the use of manual dragonfly model tractors, an idea arose to make a remote control device for a 2-wheeled tractor using Arduino. Where this tractor is equipped with several additional sensors such as ultrasonic sensors as obstacle detection, temperature sensors, potentiometers as position sensors and data storage modules. These sensors are controlled by the Arduino Uno ATmega 328p Microcontroller. Based on the tests that have been carried out, the use of the tractor control device is able to speed up and simplify the tillage process with the right results. The purpose of this research is to get performance effectiveness on the use of 2-wheeled tractors in cultivating agricultural land.